A Water Pumping Photovoltaic Powered System Based on a Merged DC-DC Sepic-Cuk Converter - Cordeiro, Armando; Foito, Daniel José Medronho (My University, 2019)
This paper has the purpose to present a non-isolated dual output DC-DC converter for a water pumping photovoltaic powered system. The proposed topology is based in the integration of a traditional Sepic and Cuk converters but requires only a single power semiconductor switch. It is characterized by an extension of the voltage static gain when compared with the classical boost topology and by a reduced voltage stress across the power switch and diodes. The system will be implemented through a classical MPPT algorithm that will control the proposed DC-DC converter. Several simulation and experimental results are also presented in order to confirm the characteristics of the proposed power converter and global water pumping systems.
Trabalho apresentado em 2019 8th International Conference on Renewable Energy Research and Applications (ICRERA), 3-6 novembro 2019, Brasov, Romenia
Keywords: DC-DC converter; Sepic converter; Cuk converter; Water pump; Photovoltaic panel